2016
DOI: 10.1098/rsob.160241
|View full text |Cite
|
Sign up to set email alerts
|

Human selenoprotein P and S variant mRNAs with different numbers of SECIS elements and inferences from mutant mice of the roles of multiple SECIS elements

Abstract: Dynamic redefinition of the 10 UGAs in human and mouse selenoprotein P (Sepp1) mRNAs to specify selenocysteine instead of termination involves two 3′ UTR structural elements (SECIS) and is regulated by selenium availability. In addition to the previously known human Sepp1 mRNA poly(A) addition site just 3′ of SECIS 2, two further sites were identified with one resulting in 10–25% of the mRNA lacking SECIS 2. To address function, mutant mice were generated with either SECIS 1 or SECIS 2 deleted or with the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 92 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…To test the function of SECIS1 and SECIS2 in vivo , we took advantage of two knockout mouse models, which are deleted for SECIS1 and SECIS2, respectively ( 32 ). As SELENOP is produced at high levels in hepatocytes for secretion into plasma, livers from wild type and SECIS deleted mice were excised and analysed by ribosome profiling and RNA-Seq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To test the function of SECIS1 and SECIS2 in vivo , we took advantage of two knockout mouse models, which are deleted for SECIS1 and SECIS2, respectively ( 32 ). As SELENOP is produced at high levels in hepatocytes for secretion into plasma, livers from wild type and SECIS deleted mice were excised and analysed by ribosome profiling and RNA-Seq.…”
Section: Resultsmentioning
confidence: 99%
“…Mice used in this study consisted of C57BL/6 (wild type) and two SECIS deletions strains, Sepp1 ΔSECIS1 and Sepp1 ΔSECIS2 , previously described ( 32 ). Whole livers were excised from male mice ( n = 3) and rapidly frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, further analysis of the SELENOP 3Ј UTR showed that deletion of SECIS-1 resulted in complete loss of processive Sec incorporation in favor of early termination at the second UGA, whereas deletion of SECIS-2 had little or no impact on SELENOP production (18,19). A similar study in mice showed the same result in terms of processivity, but overall production of SELENOP was reduced for the SECIS-2 deletion (20). Given that both SELENOP SECIS elements contain the conserved core motifs and are capable of Sec incorporation, we sought to determine which features within a SECIS element are required for processive Sec incorporation.…”
Section: Rna Stem Loop Structures Have Been Frequently Shown To Regulmentioning
confidence: 87%